Female Socialization in Anita Desai’s Clear Light of Day : : A Postcolonial Feminist Study - Najiba Hasan Ahmed; Saman Salah Hassan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
By studying Clear Light of Day (1980), this research attempts to spotlight the position of Hindu women within the patriarchal society. It presents socialization as a pillar of patriarchal perpetuation. Desai proposes an alternative form of socialization, wherein females are bestowed with a limited degree of autonomy in the construction of their individualistic persona, as exemplified through the protagonist as a contemporary woman. Employing postcolonial feminist theory, this study shows the heterogeneity of women’s experiences by scrutinizing Das’ daughters. They are brought up within the same middle-class family but have different standpoints concerning their chosen role models, which shapes their future consciousness concerning women’s position. Education plays a vital role in women’s lives since it acts as a tool to obtain economic, cognitive, academic, social, and political objectives.